Framework multimídia para apoio a Terapia do Espelho utilizando smartphone e realidade aumentada - Magagnatto, Yuri Nehase Z. G.; Pimentel, Maria da Graça C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
The popularization of mobile applications enabled the development of solutions for several areas such as mobile technologies for healthcare. This study investigates the use of computational resources to support the rehabilitation of patients in therapeutic treatment based on the mirror therapy. The mirror therapy presents relevant results in the rehabilitation of individuals who report phantom limb pain or in rehabilitation after Stroke, among others. The literature reports computational solutions that allow visualization of the healthy limb using conventional expensive augmented reality technologies. This work aimed to investigate a computational solution for the remote monitoring of mirror therapy with the support of low cost augmented reality resources. The results obtained include a computational model for smartphone and Google Cardboard. Mirror therapy specialists considered our contribution of great potential to reach the elderly and children, given their difficulty in focusing their attention when using conventional mirrors.